Menciptakan Sinergi: Lingkungan Kerja dan Motivasi untuk Kinerja Optimal - Hardiani, Hardiani; Hasyim, Hasyim; Muhammad Tafsir (Al-Buhuts, 2024)
This research was conducted with the aim of testing and analyzing the effect of work environment and work motivation on employee performance at BPSDM South Sulawesi province. The data used in this research is primary data collected by distributing questionnaires to respondents. The type of data used is quantitative data, the population is all BPSDM employees of South Sulawesi Province, totaling 140 people, while the sample taken is 60 respondents/Employees of BPSDM South Sulawesi Province. obtained by purposive sampling method. The results of the questionnaire have been tested for validity, reliability test, classic assumption test (consisting of normality test, multicollinearity test and heteroscedasticity test), multiple linear regression analysis method, hypothesis testing (which consists of t-test), correlation coefficient test and coefficient test. determination. The data in this study were processed using SPSS version 26. The results showed that the work environment and work motivation partially had a positive and significant effect on employee performance.